UNIVERSITASISASI STAIN MALANG: Analisis Kebijakan Publik Perubahan Kelembagaan Dalam Perspektif Filsafat Nilai - Esha, Muhammad In’am (ULUL ALBAB Jurnal Studi Islam, 2012)
This paper examines to study institutional change of the State Islamic University (SIU), Malang. This study gets some summaries: First, that institutional change of SIU indicates that social sphere of higher education coloured with struggle for implementation of Islamic universality in education field.   Struggle in social sphere of higher education cannot be discharged from spirit of Islam people to make a "more active" social sphere in Indonesia society. Spirit of universalization of Islamic values cannot be discharged from event pushing universitization of SIHE in the early 21 C. Second, successness of institutional change in SIU, Malang because: (a) its elite actors able to mobilize its modalities both economic, social, culture, symbolic, spiritual, political, and leadership capitals; (b) there is braveness from elit actors to put a window of opportunity as institutional actor for implementation of MoU between Minitry of Religious Affairs, Indonesia and Ministry of Education, Sudan by transform State of Islamic College of Malang (SICM) become Indonesia-Sudan Islamic University (ISIU).  This Institutional change from SICM to ISIU, actually as an opportunity transformation from institutional problem toward international problem.